2020
DOI: 10.1161/atvbaha.120.314301
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of Glycoprotein VI Promotes Thrombus Disaggregation in the Absence of Thrombin

Abstract: Objective: Atherothrombosis occurs upon rupture of an atherosclerotic plaque and leads to the formation of a mural thrombus. Computational fluid dynamics and numerical models indicated that the mechanical stress applied to a thrombus increases dramatically as a thrombus grows, and that strong inter-platelet interactions are essential to maintain its stability. We investigated whether GPVI-mediated platelet activation helps to maintain thrombus stability by using real-time video-microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
2
44
1
Order By: Relevance
“…[3][4][5][6][7] We have shown that human GPVI activates platelets on immobilized fibrinogen and that this process is key for the progression and stability of human thrombi. 7,8 In sharp contrast, we observed that mouse GPVI does not promote such an activation, as platelets deposited on fibrinogen do not fully spread. 7 In this study, we investigated the consequence of absence of GPVI/fibrinogen-mediated platelet activation in mice on the regulation of thrombosis in comparison to the human system.…”
Section: Introductioncontrasting
confidence: 62%
“…[3][4][5][6][7] We have shown that human GPVI activates platelets on immobilized fibrinogen and that this process is key for the progression and stability of human thrombi. 7,8 In sharp contrast, we observed that mouse GPVI does not promote such an activation, as platelets deposited on fibrinogen do not fully spread. 7 In this study, we investigated the consequence of absence of GPVI/fibrinogen-mediated platelet activation in mice on the regulation of thrombosis in comparison to the human system.…”
Section: Introductioncontrasting
confidence: 62%
“…Stimulation of the GPVI receptor is distinct from the other platelet activation pathways traditionally targeted by antiplatelet therapy. GPVI inhibitors, including antibodies and GPVI-Fc fusion proteins such as “Revacept”, have demonstrated effectiveness as antiplatelet agents that do not lead to bleeding complications and can assist with disaggregation of thrombi 41 , 44 . Our study indicates that colchicine targets platelet aggregation and platelet activation (ROS generation) through the GPVI pathway, thereby providing an alternate treatment option that is also known for its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…GPVI is stimulated by collagen released or exposed from within the subendothelial matrix upon injury to the endothelium and by fibrinogen and fibrin that is present during thrombus formation, among other ligands 39 . Recent studies have identified that anti-GPVI therapy can lead to disaggregation of thrombus in the absence of thrombin 41 .…”
Section: Introductionmentioning
confidence: 99%
“…To allow evaluation of the stability and embolization phase, the experimental setup has to be adapted, notably by replacing perfusion of blood with buffer. 11 At the molecular level, because the surface used to generate platelet aggregation is fibrillar collagen, the most commonly used flow-based assays tend to overemphasize the importance of collagen receptors glycoprotein VI (GPVI) and integrin α2β1 in the process of platelet aggregation and thrombosis. 12,13 This has been nicely illustrated by the group of Zaverio Ruggeri, which confirmed that GPVI plays a central role in thrombus formation on immobilized collagen, but was dispensable in a model of thrombus formation on a fibroblast and endothelial cell matrix, which might better reflect an injured vessel.…”
Section: The Development Of In Vitro Flow-based Assays In the 1980smentioning
confidence: 99%
“…The classical in vitro flow device is best suited to study the early steps involved in thrombus formation and growth. To allow evaluation of the stability and embolization phase, the experimental setup has to be adapted, notably by replacing perfusion of blood with buffer 11 …”
Section: Introduction To the In Vitro Thrombus Formation Modelmentioning
confidence: 99%